44 bicycles for Orang Asli Kids - Siti Sarah, Mohamad Rajimi (2017)
Hectic lecture schedule that just started does not stop 100 UMP volunteers to get involve in Let’s Get Together Program held at Perkampungan Orang Ali Batu 14, Gambang recently.